2006
DOI: 10.1111/j.1349-7006.2006.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II adenoviral p53 gene therapy for chemoradiation resistant advanced esophageal squamous cell carcinoma

Abstract: We investigated the feasibility, safety, biological activity and therapeutic efficacy of adenovirus-mediated p53 gene transfer in patients with chemoradiation resistant advanced esophageal carcinoma. Eligible patients were not surgical candidates and had measurable, advanced squamous cell carcinoma of the esophagus that was resistant to chemoradiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…Therapies targeting TP53 loss of function are currently being examined in clinical trials, and several studies suggest that patients harboring TP53 alterations will respond better to angiogenesis inhibitors [45] . The efficacy of intra-tumor injection of p53 adenovirus (Advexin, Introgen Therapeutics Inc., Austin, TX, United States) has been confirmed in Japanese ESCC patients [46] . Additionally, a TP53 adenoviral-based treatment (Gendicine, Shenshen Sibiono Genetech, Shenzhen, China) for patients with squamous cell carcinoma of the head and neck has recently been approved for use in China [47] .…”
Section: P53 Familymentioning
confidence: 99%
“…Therapies targeting TP53 loss of function are currently being examined in clinical trials, and several studies suggest that patients harboring TP53 alterations will respond better to angiogenesis inhibitors [45] . The efficacy of intra-tumor injection of p53 adenovirus (Advexin, Introgen Therapeutics Inc., Austin, TX, United States) has been confirmed in Japanese ESCC patients [46] . Additionally, a TP53 adenoviral-based treatment (Gendicine, Shenshen Sibiono Genetech, Shenzhen, China) for patients with squamous cell carcinoma of the head and neck has recently been approved for use in China [47] .…”
Section: P53 Familymentioning
confidence: 99%
“…Our clinical study with Ad-p53 for esophageal carcinoma, however, could not support the assumption because of its limited patient numbers. 4 Esophageal carcinoma cells with the wild-type p53 tend to express CAR better than those with mutated p53, which has not been evidenced by other types of tumors, and this putative relationship needs further studies with more esophageal specimens. We also believe that clinical studies conducted for other cancer types using Ad-p53 require re-evaluation of the efficacy from the standpoint of CAR expression levels.…”
Section: Discussionmentioning
confidence: 94%
“…We reported that Ad-p53 produced cytotoxic effects for esophageal carcinoma cells and have recently completed a phase I/II clinical trial for cancer patients with Ad-p53. 3,4 The clinical study showed that intratumoral injection of Ad-p53 was safe and produced antitumor effects with variable efficacy. 4 Multiple mechanisms of the Ad-p53-mediated antitumor activities are well demonstrated and apoptosis induction is one of the direct actions of tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] When used as vaccine vectors, on the other hand, Ad vectors are intramuscularly injected. 27,28 In addition, Ad vectors are intramyocardially injected in angiogenic gene therapy.…”
Section: Spleen and Nasal Cavitymentioning
confidence: 99%